FA1 Induces Pro-Inflammatory and Anti-Adipogenic Pathways/Markers in Human Myotubes Established from Lean, Obese, and Type 2 Diabetic Subjects but Not Insulin Resistance - Abdallah, Basem M.; Beck-Nielsen, Henning; Gaster, Michael (Frontiers in Endocrinology, 2013)
Aims: Delta like 1/FA1 (Dlk1/FA1) is a protein secreted by hormone producing cells in adult human and mice that is known to inhibit adipogenesis. Recent studies demonstrated the role of Dlk1/FA1 in inducing insulin resistance in mice. To investigate the involvement of circulating Dlk1/FA1 in insulin resistance and type 2 diabetes in human subjects, we studied the effects of chronic FA1 on the intermediary metabolism in myotubes established from lean, obese and type 2 diabetic (T2D) subjects. Methods: Myotube cultures were established from lean and obese control subjects, and obese T2D subjects and treated with soluble FA1 for 4 days supplemented with/without palmitate (PA). Lipid- and glucose metabolism were studied with labelled precursors while quantitative expression of genes was analyzed using Real-Time PCR. Results: Diabetic myotubes express significantly reduced insulin-stimulated glucose metabolism compared to lean myotubes and a significantly decreased basal PA oxidation. Chronic FA1 exposure did not affect the intermediary metabolism in myotubes. Insulin sensitivity of glucose and lipid metabolism was not affected by chronic FA1 exposure in myotubes established from lean, obese and T2D subjects. Instead, chronic FA1 exposure induced pro-inflammatory cytokines expression (IL6 and CCL2) in association with reducing adipogenic markers (ADD1, AP2, CD36 and PPARg2) in myotubes. Consistent with this observation, addition of FA1 to cultured myotubes was show to significantly inhibit their differentiation into adipocyte. Conclusions: Our results exclude direct effects of FA1 on glucose and lipid metabolism in cultured myotubes established from lean, obese and type 2 diabetic subjects. Therefore, the pathogenesis of FA1-indued IR might mainly be mediated via the FA1-induced stimulation of pro-inflammatory cytokines, which on turn inhibit adipogenesis in human myotubes.